KERJASAMA JEPANG-INDONESIA MELALUI JAPAN INTERNATIONAL CORPORATION AGENCY(JICA) DI CAGAR BIOSFER GIAM SIAK KECIL-BUKIT BATU, KABUPATEN BENGKALIS (2012-2014) - Sinaga, Nike Astria; Fachri, Yuli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This study aimed to describe the assistance of JICA as one form ofbilateral relations between Japan and Indonesia. This study also aims to lookat the prospect of JICA's assistance in the environmental field in RiauProvince. This study is limited in the span of 2011 to 2014 and more focuseddiscuss the JICA cooperation with the Riau provincial and regency Bengkalisin the environmental field. Writing this thesis uses qualitative researchmethods, descriptive and research techniques used by the author is literature.The results showed that with the implementation of the cooperationbetween Japan-Indonesia through JICA, namely the provision of technicalassistance in pengelolaaan and handling of GSK-BB Biosphere Reserveineffective. This is indicated by the absence of positive results were sosignificant after inclusion of JICA and the establishment of cooperationbetween the Japan-Indonesia. Even in the years 2013-2014 still damage andencroachment in the conservation area. Even in view of growth and grazingdamage seen from reaching 1.18% in 2012-2014.Keywords : Riau Province, Biosphere Reserve of GSK-BB, JICA